Pengaruh Gaya Kepemimpinan, Kompensasi dan Lingkungan Kerja Terhadap Motivasi Guru SMK Tunas Harapan di Plupuh Kabupaten Sragen - Junti Ayu Ariyani; Lamidi (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The development of superior human resources is the key to success in achieving national development goals. High work motivation is one of the determining factors in optimising individual and organisational performance. This study intends to examine the extent to which the variables of leadership style, compensation, and work environment influence the level of work motivation of teachers at SMK Tunas Harapan in Plupuh, Sragen Regency. All teachers at SMK Tunas Harapan were used as the population in this study. Data collection was carried out thoroughly on all members of the population (census) so that a sample of 58 respondents was obtained. Quantitative data analysis in this study uses multiple linear regression models. Previously, classical assumption testing was carried out, then t-test, F-test and coefficient of determination (R2). Statistical analysis using the t-test shows the significance of the variables of leadership style, compensation, and work environment on teacher work motivation at SMK Tunas Harapan Plupuh. The F-test results also confirm the accuracy of the regression model used in this study.